Issues in the estimation of dynamic happiness models: A comment on "Does childhood predict adult life satisfaction?" - Alan T. Piper; Geoffrey T. Pugh (Economics: The Open-Access, Open-Assessment E-Journal, 2016)
This paper offers methodological comments on a recent (November 2014) Economic Journal article. The comments consider its use of a dynamic model - the inclusion of a lagged dependent variable - and its approach to estimation. By way of critique, the authors highlight general issues regarding dynamic panel analysis that are still less fully appreciated in the economics of happiness literature than elsewhere in economics and other quantitative social sciences. This discussion of methodological issues arising from dynamic estimation may be of practical assistance to researchers new to the field and/or to dynamic modelling.
Keywords: I31; 330; life Satisfaction; dynamic panel analysis; GMM